Techno – Economic Analysis of Rooftop Solar Panel Uprating on Commercial Building (Casestudy on Karawang Branch Office of XYZ Company) - Aji Nur Widyanto; Muhamad Arya Krisna Adhi; Faiz Husnayain; Agus R Utomo; I Made Ardita (Universitas Ahmad Dahlan, 2023)
On April 22nd, 2016, Indonesia signed the Paris Agreement, which goal is that the world will enter the net-zero emission phase in 2060. To support that, it is better to increase the solar rooftop capacity have been installed. In this study, there are some variations, such as the capacity of solar rooftops based on load profile and installed power (75%, 90%, and 100%), variation of solar module placement, and variation of solar module types. The result shows that to fulfill the load needs, it will need 40 kW of inverter capacity and 49.5 kWp of PV capacity with a total module of 113 pcs. Based on the solar module type simulations result, the 440 Wp B – brand has the highest performance result among the others. Uprating solar rooftop capacity will cost around Rp.1,138,529,870 for the investment, and the payback period is around 18 years. This study finds that uprating the capacity of rooftop solar panel can reduce electricity tariffs and increase energy production. Moreover, the results of the economic analysis revealed that the initial cost, interest rate, and electricity price will play crucial roles in determining whether to launch a project or not.